Gender and food systems: Avenues for transformation? - Quisumbing, Agnes R.; Heckert, Jessica; Malapit, Hazel J.; Meinzen-Dick, Ruth S.; Raghunathan, Kalyani; Seymour, Greg; Faas, Simone; Myers, Emily (AKADEMIYA2063, 2023)
Worldwide, approximately 1.23 billion people are employed in agrifood systems, and 3.83 billion live in households that are linked to or reliant on these systems in some way (Davis et al. 2023). In Africa, experts estimate that between two-thirds and four-fifths of all jobs are in agrifood systems; nonagricultural agrifood system jobs account for only a small portion of this employment and are mainly concentrated in urban areas (Davis et al. 2023). Population growth and rapid urbanization, the growing risks of climate change, and persistent problems of malnutrition all mean that rural and urban African agrifood systems need to transform both substantially and rapidly to achieve the goals of sustainable, equitable, and healthy food systems.